Receipt of Glucose Testing and Performance of Two US Diabetes Screening Guidelines, 2007-2012. - Kai McKeever Bullard; Mohammed K Ali; Giuseppina Imperatore; Linda S Geiss; Sharon H Saydah; Jeanine B Albu; Catherine C Cowie; Nancy Sohler; Ann Albright; Edward W Gregg (PLoS ONE, 2015)
Screening guidelines are used to help identify prediabetes and diabetes before implementing evidence-based prevention and treatment interventions. We examined screening practices benchmarking against two US guidelines, and the capacity of each guideline to identify dysglycemia.Using 2007-2012 National Health and Nutrition Examination Surveys, we analyzed nationally-representative, cross-sectional data from 5,813 fasting non-pregnant adults aged ≥20 years without self-reported diabetes. We examined proportions of adults eligible for diagnostic glucose testing and those who self-reported receiving testing in the past three years, as recommended by the American Diabetes Association (ADA) and the US Preventive Services Task Force (USPSTF-2008) guidelines. For each screening guideline, we also assessed sensitivity, specificity, and positive (PPV) and negative predictive values in identifying dysglycemia (defined as fasting plasma glucose ≥100 mg/dl or hemoglobin A1c ≥5.7%).In 2007-2012, 73.0% and 23.7% of US adults without diagnosed diabetes met ADA and USPSTF-2008 criteria for screening, respectively; and 91.5% had at least one major risk factor for diabetes. Of those ADA- or USPSTF-eligible adults, about 51% reported being tested within the past three years. Eligible individuals not tested were more likely to be lower educated, poorer, uninsured, or have no usual place of care compared to tested eligible adults. Among adults with ≥1 major risk factor, 45.7% reported being tested, and dysglycemia yields (i.e., PPV) ranged from 45.8% (high-risk ethnicity) to 72.6% (self-reported prediabetes). ADA criteria and having any risk factor were more sensitive than the USPSTF-2008 guideline (88.8-97.7% vs. 31.0%) but less specific (13.5-39.7% vs. 82.1%) in recommending glucose testing, resulting in lower PPVs (47.7-54.4% vs. 58.4%).Diverging recommendations and variable performance of different guidelines may be impeding national diabetes prevention and treatment efforts. Efforts to align screening recommendations may result in earlier identification of adults at high risk for prediabetes and diabetes.